2017
DOI: 10.1111/ans.13969
|View full text |Cite
|
Sign up to set email alerts
|

Influence of primary site on metastatic distribution and survival in stage IV colorectal cancer

Abstract: Rectal cancers have a higher chance of recurring, with a higher metastatic rate to the lung, yet demonstrate better survival outcomes in metastatic colorectal cancer, reflecting the benefit of intervention for metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(39 reference statements)
3
13
0
Order By: Relevance
“…Considering the primary tumor location of SCLM patients, SCLM patients with right-sided tumor location were associated with obviously poorer prognosis than those with other tumor sites. Similar results had been reported by some previous studies ( 13 , 14 , 16 , 17 ). Compared with left-sided colorectal tumors, the liver metastatic area of right-sided tumors seemed to be more extensive, indicating that these patients had significantly worse prognoses ( 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…Considering the primary tumor location of SCLM patients, SCLM patients with right-sided tumor location were associated with obviously poorer prognosis than those with other tumor sites. Similar results had been reported by some previous studies ( 13 , 14 , 16 , 17 ). Compared with left-sided colorectal tumors, the liver metastatic area of right-sided tumors seemed to be more extensive, indicating that these patients had significantly worse prognoses ( 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…The prevalent association, observed in the current study, between primary tumor location and the three subcategories of stage IV mCRC could also represent an explanation for the higher survival observed in left-sided mCRC than in rightsided tumors [1][2][3]. Thus, patients with metastatic RCC have the highest probability of developing stage IVC disease and the lowest probability for stage IVA disease.…”
Section: Discussionsupporting
confidence: 58%
“…Until the last years, CRC was considered a unitary entity, but quite recently, some studies have demonstrated that there are differences in the prognosis of patients with Abbreviations: AJCC: American Joint Committee on Cancer; BRAF: v-raf murine sarcoma viral oncogene homolog B; CRC: colorectal cancer; CT: computed tomography; DW-MRI: diffusion-weighted -magnetic resonance imaging; IQR: interquartile range; LCC: left colon cancer; M1a: metastasis to one organ/site, excluding peritoneum; M1b: two or more metastatic sites without peritoneal involvement ; M1c: peritoneal metastases; mCRC: metastatic CRC; OS: overall survival; PET: positron emission tomography; RCC: right colon cancer; RC: rectal cancer; RR: relative risk; SD: standard deviation. metastatic colorectal cancer (mCRC), depending on the location of the primary tumor (between the right colon vs. the left colon and the rectum) [1][2][3]. During recent years, some explanations have emerged, such as the different embryological origin of the right colon versus the left colon and the rectum, the distinct pattern of somatic mutations in adenocarcinomas located on the right side versus left-sided CRC and the differences in the microbiota [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously the suggestion has been made that the typically more indolent course of presentation of right CRC, might in part be responsible for inferior outcome with resulting liver metastases[ 10 ]. The notion here is that delayed diagnosis of primary tumour results in an increased risk of developing synchronous metastases which are then incurable[ 51 ]. This would mean potentially fewer curative-intent resections offered to these patients, resulting in observed abbreviated survival.…”
Section: Discussionmentioning
confidence: 99%